2018
DOI: 10.1111/sode.12281
|View full text |Cite
|
Sign up to set email alerts
|

You've got a friend(ly school): Can school prosocial norms and friends similarly protect victims from distress?

Abstract: Testing the potential protective effects of school-level prosocial norms and having friends on peer victimization-related distress, this study examined whether one protective factor is particularly important in the absence of the other. An ethnically diverse sample (N 5 5,991) from 26 middle schools reported on peer prosocial behavior, social anxiety, loneliness, and perceived school safety; peer nominations assessed victimization and friends. Multilevel analyses revealed that sixth grade friendless victims fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
(59 reference statements)
0
15
1
Order By: Relevance
“…The negative effect of hostile environments is reflected in earlier research on bullying and peer aggression, showing the negative mental health consequences of witnessing bullying at school for nonvictim students (Rivers et al, 2009) and becoming more aggressive from being in an aggressive environment (Henry et al, 2000). Being in a hostile environment can thus elevate feelings of threat for those who are individually victimized (Schacter & Juvonen, 2018b), especially for those who already have deterministic beliefs that they are unable to escape victimization. By contrast, adolescents who endorse an incremental theory, believing that it is possible for their victimization to change, may not consider having more fellow victims as a potent threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effect of hostile environments is reflected in earlier research on bullying and peer aggression, showing the negative mental health consequences of witnessing bullying at school for nonvictim students (Rivers et al, 2009) and becoming more aggressive from being in an aggressive environment (Henry et al, 2000). Being in a hostile environment can thus elevate feelings of threat for those who are individually victimized (Schacter & Juvonen, 2018b), especially for those who already have deterministic beliefs that they are unable to escape victimization. By contrast, adolescents who endorse an incremental theory, believing that it is possible for their victimization to change, may not consider having more fellow victims as a potent threat.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, being victimized in an unsafe, high-victimization environment is harmful because it creates the perception that escaping victimization is almost inevitable and that one needs to be constantly vigilant to a strong threat. It was shown that witnessing bullying at school predicted risks to mental health over and above direct experiences of victimization (Rivers, Poteat, Noret, & Ashurst, 2009), that schools in which aggression was considered more normative were linked to greater individual aggression (Henry et al, 2000), and that victims in schools with lower prosocial (i.e., helping each other) norms felt more distressed and perceived their school climate as more unsafe (Schacter & Juvonen, 2018b).…”
Section: Many Fellow Victims Hypothesismentioning
confidence: 99%
“…In the same line, future studies can examine classroom norms, for example, whether aggressive peers are popular in the classroom and whether students really act against victimization and defend each other in these situations. For instance, a recent study found that both prosocial school norms and having friends buffer against the negative effects of victimization (Schacter & Juvonen, 2018b). Finally, as girls often focus more on prosocial behaviors and boys behave more aggressively than girls, future studies might include interaction effects between students’ gender and friendships selection and influence processes.…”
Section: Discussionmentioning
confidence: 99%
“…When aggression is endorsed by popular peers, students tend to be reluctant to behave against this norm nor do they feel the urge to intervene in bullying (Peets et al, 2015). This possibly enhances victims' feeling that nobody cares about them (Schacter & Juvonen, 2018). Consequently, victims may feel worse when aggressive popularity norms are higher (Hypothesis 2b).…”
Section: Aggressive Norms and Victimized Childrenmentioning
confidence: 99%
“…It is possible that when aggression is endorsed by popular peers, students are less likely to behave against this norm, nor intervene in bullying (Peets et al, 2015)-perhaps because they fear becoming a victim themselves or because they view the aggressive behaviors in a positive light and therefore do not feel the need to intervene. This possibly enhances victims' feeling that nobody cares about them (Schacter & Juvonen, 2018), and hence, results in enhanced school maladjustment among victims.…”
Section: Aggressive Norms and Victimized Childrenmentioning
confidence: 99%